2022
DOI: 10.1073/pnas.2107567119
|View full text |Cite
|
Sign up to set email alerts
|

cAMP and voltage modulate rat auditory mechanotransduction by decreasing the stiffness of gating springs

Abstract: Hair cells of the auditory and vestibular systems transform mechanical input into electrical potentials through the mechanoelectrical transduction process (MET). Deflection of the mechanosensory hair bundle increases tension in the gating springs that open MET channels. Regulation of MET channel sensitivity contributes to the auditory system’s precision, wide dynamic range and, potentially, protection from overexcitation. Modulating the stiffness of the gating spring modulates the sensitivity of the MET proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…The LPHN2-mediated auditory MET is more similar to the signalling mechanism for smell perception than to that for visual perception, which relies mainly on the Gt-mediated inhibition of constitutive cGMP levels in photoreceptor cells. Consistent with our findings, cAMP has been proposed to modulate the sensitivity of the MET in cochlear hair cells (Mecca et al, 2022). Notably, a loss-of-function mutation in adenylyl cyclase 1 (AC1) caused by the deletion of the C-terminal 82 amino acids is linked to hearing loss in humans (Santos-Cortez et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The LPHN2-mediated auditory MET is more similar to the signalling mechanism for smell perception than to that for visual perception, which relies mainly on the Gt-mediated inhibition of constitutive cGMP levels in photoreceptor cells. Consistent with our findings, cAMP has been proposed to modulate the sensitivity of the MET in cochlear hair cells (Mecca et al, 2022). Notably, a loss-of-function mutation in adenylyl cyclase 1 (AC1) caused by the deletion of the C-terminal 82 amino acids is linked to hearing loss in humans (Santos-Cortez et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Spatial confinement through inclusion in local signalosomes as a mechanism to secure specificity of response is not exclusive to PKA and has also been shown for other cAMP effectors, including the exchange factor directly activated by cAMP (EPAC) proteins (153)(154)(155)(156) and the Popeye domain-containing (POPDC) proteins (157,158). Given that these effectors modulate their own distinct cellular functions, they are also expected to be activated locally by confined pools of cAMP.…”
Section: Signaling By Camp Nanodomainsmentioning
confidence: 96%
“…In response to magnetic stimulation, the tension force was produced by magnetic beads attached to the N-terminus of selected aGPCRs, and the activation of Gs or Gi signaling downstream of mechanosensitive GPCRs was measured by BRET signals. The Gs/Gi signal was selected as a readout because recent studies have indicated critical roles of Gi protein and cAMP levels in the regulation of stereocilium development, vestibular function and hair cell mechanotransduction [37][38][39] . Using this system, we revealed that 5 receptors (GPR133, GPR126, LPHN2, LPHN3 and VLGR1) activated Gi signaling in response to force stimulation, whereas 3 receptors (GPR133, LPHN2 and VLGR1) activated Gs signaling in response to force application (Figure 1D).…”
mentioning
confidence: 99%